2019
DOI: 10.3389/fendo.2019.00161
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Creatine Supplementation in Gilthead Seabream (Sparus aurata) Increases Dorsal Muscle Area and the Expression of myod1 and capn1 Genes

Abstract: Creatine (Cr) is an amino acid derivative with an important role in the cell as energy buffer that has been largely used as dietary supplement to increase muscle strength and lean body mass in healthy individuals and athletes. However, studies in fish are scarce. The aim of this work is to determine whether dietary Cr supplementation affects muscle growth in gilthead seabream ( Sparus aurata ) juveniles. Fish were fed ad libitum for 69 days with diets containing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Myf5 expression was extremely low in Mth-3 during the cultivation process ( Figures 3a and 3b ). Previous studies demonstrated that Myf5 and MyoD can complement each other in function [ 16 , 25 ], therefore, we speculated that the differentiation of SMSCs in Mth-3 was mainly regulated by MyoD, whereas in Mth-15, the expressions of Myf5 and MyoD were high and thus both may regulate cell differentiation. On day 5, the expression of Myf5 in Mth-15 was significantly higher than in Mth-3 (p<0.05).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Myf5 expression was extremely low in Mth-3 during the cultivation process ( Figures 3a and 3b ). Previous studies demonstrated that Myf5 and MyoD can complement each other in function [ 16 , 25 ], therefore, we speculated that the differentiation of SMSCs in Mth-3 was mainly regulated by MyoD, whereas in Mth-15, the expressions of Myf5 and MyoD were high and thus both may regulate cell differentiation. On day 5, the expression of Myf5 in Mth-15 was significantly higher than in Mth-3 (p<0.05).…”
Section: Resultsmentioning
confidence: 93%
“…Myf5 expression was extremely low in Mth-3 during the cultivation process (Figures 3a and 3b). Previous studies demonstrated that Myf5 and MyoD can complement each other in function [16,25], therefore, we speculated that the differentiation of SMSCs in Mth-3 was mainly regulated by MyoD, whereas in Mth-15,…”
Section: Effect Of Sheep Slaughter Age On Mrf Expression In Smscsmentioning
confidence: 91%
“…In human applications, creatine monohydrate powder (CAS No. : 6020‐87‐7) is the most commonly used form since the early 1990s 23,49,55 . Other formulations include creatine hydrochloride and, recently, a co‐amorphous formulation of creatine and citric acid, which has a better solubility in water 56 .…”
Section: Application Form Of Creatinementioning
confidence: 99%
“…The MRFs include four transcription factors, myogenic determining factor (MyoD), myogenic factor5 (Myf5), muscle regulatory factor‐4 (Mrf4) and myogenin (Myog) (see Table 2). Key factors in the development of skeletal muscle have been shown to be stimulated by creatine supplementation 22–24 …”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of muscle fibers include muscle fiber diameter and muscle fiber density. Generally, muscle fiber diameter and muscle fiber density are negatively correlated [ 2 , 3 ]. The more muscle fibers per unit area, the greater the density of muscle fibers and the more tender the meat [ 4 ].…”
Section: Introductionmentioning
confidence: 99%